ANALISIS SUMBER DAN PENGGUNAAN MODAL KERJA PADA PT. BANK RAKYAT INDONESIA,TBK - CHRISTOFEL MANOPO, FRANS; MONTOLALU, JOHNY; S. MANOPPO, WILFRIED (Sam Ratulangi University, 2016)
Abstract. The purpose of this study was to analyze and determine the level of effectiveness and efficiency sources and uses of working capital at PT. Bank Rakyat Indonesia, Tbk. The period of 2010 s / d 2012The analytical method used is descriptive analysis method using a capital adequacy ratio of work consisting of three types of ratio is the ratio of total assets to net working capital, current liabilities to net working capital and working capital turnover. The calculation of the ratio obtained data in 2010 Total Asset To Net Working Capital Ratio is 9.02, Current Liabilities To Net Working is 8.14, Working Capital Turnover is 1.13. in 2011 Total Asset To Net Working Capital Ratio is 7.82, Current Liabilities To Net Working Capital is 6.93, Working Capital Turnover is 0.93. In 2012 Total Asset To Net Working Capital Ratio is 7.78, Current Liabilities To Net Working Capital is 6.84, Working Capital Turnover is 0.83Based on that data as a whole of the analytical method used in analyzing the sources and uses of working capital at PT. Bank Rakyat Indonesia, Tbk is a comparative analysis of financial statements up to the evaluation of capital adequacy ratio, the level of effectiveness and efficiency of working capital PT. Bank Rakyat Indonesia, Tbk awake so in the management of working capital is not going idle funds (funds that are unemployed). The data above also illustrates the level of liquidity in the PT. Bank Rakyat Indonesia, Tbk, each year has increased 0.5 s / d 1.0 point. This indicates that the capital adequacy in PT. Bank Rakyat Indonesia, Tbk, maintained its stability.Keywords: Working capital, Working Capital Resources, Use of Working Capital